Agiculture negotiations in WTO: Critical issues and Concerns - Sinha Rohit; Nataraj Geethanjali (Focus WTO, 2013)
The Doha Developement Round is currently engaged ina series of negotiations to rationalize the agricultural farm sector by undertaking substantial tariff reduction programme. There has been some movement towards rationalization. However, developing countries argue that in the event of whole hearted liberalization, most of the developing countries are going to experience significant losses in the world trade as they are not able compete in world economy due to domestic subsidy and export competition measures provided by developed countries. The paper makes an attempt to suggest how measures like SSM ans SP can be effective for developing countries in the wake of agicultural trade liberalization. It analyzes and informs that developing countries as an effective group have the ability and capacity to argue out their case in the coming Ministerial conference which can deliver some concrete results.
Keywords: SSM; WTO